Environmental Impact of Shrimp Farming: A Case Study of Coastal Community - Bipul Roy; Md. Abu Hassan; Md. Al-Amin Khan; Shakil Sheikh (Journal of Agroforestry and Environment)
Shrimp farming in the coastal area has impacts on the soil, water, air, fish habitats, agricultural farmland, grazing land, indigenous fish, household vegetation, land fertility, and mangroves. The objectives of the study were to assess the socio-economic status of the shrimp farmers and understand the environmental impact of shrimp farming in coastal areas. A structured questionnaire survey was conducted among 100 randomly selected respondents from Satkhira Sadar and Debhata Upazila. Data were analyzed using descriptive statistics to evaluate the socio-economic conditions and perceived environmental impacts. Thirty-eight percent of respondents were professional farmers. The maximum respondents reported that their monthly income is limited to 6000- 9000tk, and they are not highly educated. Ninety-six percent of respondents have no idea about air quality. Because they are not highly educated. The average water salinity is found to be 6.6 ppt, and the soil pH is relatively acidic. Most of the respondents (64%) reported that shrimp farming led to a decrease in indigenous fish, while two percent reported an increase. About twenty-six percent of the respondents indicated that shrimp farming has led to people migrating to other places for work. Despite these negative impacts, shrimp farming can be sustainable and environmentally friendly if proper practices are implemented, such as the use of organic feed instead of industrial feed, periodic monitoring of water salinity, and training farmers on environmentally sound waste disposal methods. These suggestions are based on the issues identified in the field data, including high water salinity, poor awareness of air quality, and declining indigenous fish populations. This study could help to promote more sustainable and responsible shrimp farming practices that reduce the impacts on the environment, agriculture, and human health.